Publications on Clinical Research in Otolaryngology–A Systematic Analysis of Leading Journals in 2010 - Kaper, Nina M.; Ramakers, Geerte G. J.; Aarts, Mark C. J.; van der Heijden, Geert J. M. G. (Frontiers in Surgery, 2019)
Background: We wanted to asses and characterize the volume of Otolaryngology publications on clinical research, published in major journals. Methods and Material: To assess volume and study type of clinical research in Otolaryngology we performed a literature search in high impact factor journals. We included 10 high impact factor Otolaryngology journals and 20 high impact factor medical journals outside this field (2011). We extracted original publications and systematic reviews from 2010. Publications were classified according to their research question, that is therapy, diagnosis, prognosis or etiology. Results: From Otolaryngology journals (impact factor 1.8 to 2.8) we identified 694 (46%) publications on original observations and 27 (2%) systematic reviews. From selected medical journals (impact factor 6.0 to 101.8) 122 (2%) publications related to Otolaryngology, 102 (83%) were on original observations and 2 (0.04%) systematic reviews. The most common category was therapy (40%). Conclusion: Half of publications in Otolaryngology concerns clinical research, which is higher than other specialties. In medical journals outside the field of Otolaryngology, a small proportion (2%) of publications is related to Otolaryngology. Striking is that systematic reviews, which are considered high level evidence, make up for only 2% of publications. We must ensure an increase of clinical research for optimizing medical practice.